The Effect of Parity on Efficacy and Safety Outcomes in Induction of Labor [31B]. (May 2018) - Miller, Hugh; Billips, Benjamin; Dutia, Roxanne; Soskin, Luba; Raymond, Kyle; Powers, Barbara
Abstract : INTRODUCTION: We investigated the effect of parity on induction of labor (IOL) outcomes in women treated with either misoprostol (MVI) or dinoprostone vaginal inserts (DVI). METHODS: Pooled IOL outcome data were analyzed from 3 phase II/III trials using DVI 10mg and MVI 200µg in nulliparous (DVI n=715/MVI n=522) versus parous (DVI n=390/MVI n=283) women during first hospitalization. Descriptive statistics compared demographics; logistic regression assessed the relationship between parity, treatment, and outcomes. Adverse events (AEs) investigated: 1) abnormal fetal heart rate (FHR II/III), 2) uterine tachysystole (UT), 3) abnormal FHR with/without UT (FHR/UT), 4) abnormal labor affecting the fetus (UT with FHR II/III), 5) UT or hypertonus with/without FHR II/III (UH), 6) meconium, and 7) arrested labor (AL). RESULTS: Demographics were similar between groups except parous women were older. Parity was associated with a higher odds of vaginal delivery (VD) and lower odds of Cesarean delivery (CD) compared to nulliparity (P<.001). Parous women had fewer specific AEs (FHR II/III, FHR/UT, UH, meconium, AL; P<.001). No differences in odds of VD or CD were observed between treatments. Women in both parity groups had a greater risk of UH (P<.001) if treated with MVI vs DVI, but only nullipara showed greater odds of UT with FHR II/III, FHR/UT, and meconium if treated with MVI vs. DVI (P<.05). There was no statistical evidence of an interaction between parity and treatment. CONCLUSION: Parity had improved efficacy and safety outcomes compared to nulliparity. Treatment with MVI led to greater risk of certain AEs; these were more frequently noted in nullipara.